Perception of police on discrimination in Serbia - Zekavica Radomir (Temida, 2014)
This paper presents and analyses results deriving from the research on the attitudes of criminal investigation officers in five police departments in Serbia: Belgrade, Novi Sad, Novi Pazar, Subotica and Vranje. The case studies examined the attitudes of members of criminal investigation police and their perception(s) of discrimination towards vulnerable groups. The study aimed to determine the level of animosity exhibited in speech, to analyse socio-ethnic distance, to observe reactions towards measures designed to improve the situation of vulnerable groups, to consider the relationship among institutions regarding their responsibility for the occurrence of discrimination and its impact on the reduction of it, to discuss personal experiences of discrimination and to analyse attitudes regarding certain claims of a stereotypical character. Moreover, the paper also presents a comparative analysis of similar surveys on the perception of citizens towards discrimination that have thus far been conducted in Serbia. The results demonstrated that the police in Serbia did not exhibit a particularly discriminatory attitude towards citizens. It is important to note that the most prominent socio-ethnic distances were exhibited in relation to Roma and members of the LGBT community.